IC 6659 Methods And Costs Of Dredging Auriferous Gravels At Lancha Plana, Amador County, Calif. ? Introduction And Acknowledgments - Charles G. Patmon (The National Institute for Occupational Safety and Health (NIOSH), 1932)
This paper describing the methods of dredging and treatment of gold-bearing gravels at the Lancha Plana Gold Dredging Co.'s dredge is one of a series of similar papers being prepared by the Bureau of Mines on mining practices, methods, and costs in the various mining districts of the United States. The dredge is located near the Mokelumne River, 12 miles west of San Adreas, Calif.; it is accessible by an improved dirt road from Jackson, which is about 20 miles distant.